Wheat improves the quality of coarse cereals steamed bread by changing the gluten network - Mengru Han; Jiayue Zhou; Jiale Wang; Aliaksandr Ivanistau; Qinghua Yang; Baili Feng (Applied Food Research)
Investigating the effects of coarse cereal flour addition on steamed bread quality is crucial for expanding the processing and utilization of coarse cereals while overcoming technical challenges. Therefore, in this study, the effects of blending wheat flour with rye, proso millet, buckwheat, and pea flours on the quality of steamed bread were investigated. The results demonstrated that the gluten network uniformity of the coarse cereal–wheat doughs was significantly improved compared with that of the coarse cereal doughs. The BW sample exhibited higher protein area (25.04 × 104) and number of protein junctions (12.25 × 102) than the RW, PMW, and PW samples. Compared with the coarse cereal doughs, the reconstituted doughs presented a significantly lower free sulfhydryl content but more intermolecular disulfide bonds, which enhanced gluten network formation. In addition, the appearance, nutritional quality and textural properties of the coarse cereal steamed breads were significantly different, which increases the variety of steamed bread options for consumer groups. The results offer valuable guidance for product development utilizing coarse grains to optimize nutritional profiles in staple diets.